Binding of cis-[Ru(phen)2(3,4Apy)2]2+ to Model Lipid Membranes: Implications for New Tools in the Development of Antiamyloid Drugs - da Cruz Garcia, Maria Laura; Paixão, Rafaela Ribeiro; Pazin, Wallance M. [UNESP]; Oliveira, Osvaldo N.; Cremer, Paul S.; Carlos, Rose Maria (American Chemical Society (ACS), 2024)
This study explores the interactions of the cis-[Ru(phen)2(Apy)2]2+ complex (RuApy, phen = 1,10-phenanthroline, Apy = 3,4-aminopyridine) with model lipid membranes to explain the role this complex plays in mitigating Aβ toxicity in PC12 neuronal cells. Fluorescence quenching, surface pressure isotherms in Langmuir monolayers, and infrared reflection-absorption analyses revealed that the positively charged RuApy interacts with the phosphate headgroups of monolayers, indirectly affecting ester carbonyl groups through hydrogen bonding with the amino group of the pyridine ligand of RuApy. These results offer a scenario for the protective effect of RuApy against Aβ toxicity in neuronal cells in which these interactions shield the electrostatic interactions of Aβ with lipid membranes, preserving membrane integrity and mitigating the deleterious influence of Aβ. This opens new avenues for antiamyloid strategies, focusing on compounds that prevent salt-bridge formation between bilayer membranes and amyloid proteins, aiding in the rational design of effective antiamyloid agents for therapeutic application.